Vitamin D3 inhibits expression and activities of matrix metalloproteinase-2 and -9 in human uterine fibroid cells - Halder, Sunil K. (Oxford University Press, 2013)
STUDY QUESTION: Can biologically active vitamin D3 [1,25(OH)(2)D3] regulate the expression and activity of matrix metalloproteinases (MMPs) in human uterine fibroid cells? SUMMARY ANSWER: 1,25(OH)(2)D3 effectively reduced the expression and activities of MMP-2 and MMP-9 in cultured human uterine fibroid cells. WHAT IS KNOWN ALREADY: Uterine fibroids (leiomyoma) express higher levels of MMP activity than adjacent normal myometrium, and this is associated with uterine fibroid pathogenesis. However, it is unknown whether 1,25(OH)(2)D3 can regulate the expression and activities of MMPs in human uterine fibroid cells. STUDY DESIGN, SIZE, DURATION: Surgically removed fresh fibroid tissue was used to generate primary uterine fibroid cells. PARTICIPANTS/MATERIALS, SETTING, METHODS: An immortalized human uterine fibroid cell line (HuLM) and/or primary human uterine fibroid cells isolated from fresh fibroid tissue were used to examine the expression of several MMPs, tissue inhibitors of metalloproteinases (TIMP) 1 and 2 and the activities of MMP-2 and MMP-9 after 1,25(OH)(2)D3 treatment. Real-time PCR and western blots analyses were used to measure mRNA and protein expression of MMPs, respectively. Supernatant cell culture media were analyzed for MMP-2 and MMP-9 activities using a gelatin zymography assay. MAIN RESULTS AND THE ROLE OF CHANCE: 1–1000 nM 1,25(OH)(2)D3 significantly reduced mRNA levels of MMP-2 and MMP-9 in HuLM cells in a concentration-dependent manner (P < 0.5 to P < 0.001). The mRNA levels of MMP-1, MMP-3, MMP-13 and MMP-14 in HuLM cells were also reduced by 1,25(OH)(2)D3. 1,25(OH)(2)D3 significantly reduced MMP-2 and MMP-9 protein levels in a concentration-dependent manner in both HuLM and primary uterine fibroid cells (P < 0.05 to P < 0.001). Moreover, 1,25(OH)(2)D3 increased the mRNA levels of vitamin D receptor (VDR) and TIMP-2 in a concentration-dependent manner in HuLM cells (P < 0.05 to P < 0.01). 1,25(OH)(2)D3 also significantly increased protein levels of VDR and TIMP-2 in all cell types tested (P < 0.05 to P < 0.001). Gelatin zymography revealed that pro-MMP-2, active MMP-2 and pro-MMP-9 were down-regulated by 1,25(OH)(2)D3 in a concentration-dependent manner; however, the active MMP-9 was undetectable. LIMITATIONS, REASONS FOR CAUTION: This study was performed using in vitro uterine fibroid cell cultures and the results were extrapolated to in vivo situation of uterine fibroids. Moreover, in this study the interaction of vitamin D3 with other regulators such as steroid hormone receptors was not explored. WIDER IMPLICATIONS OF THE FINDINGS: This study reveals an important biological function of 1,25(OH)(2)D3 in the regulation of expression and activities of MMP-2 and MMP-9. Thus, 1,25(OH)(2)D3 might be a potential effective, safe non-surgical treatment option for human uterine fibroids. STUDY FUNDING/COMPETING INTEREST(S): This study was primarily supported by Research Centers in Minority Institutions (RCMI)-pilot grant 2 G12 RR003032-26 to S.K.H. and supported in part by Meharry Translation Research Center/Clinical Research Center (MeTRC/CRC) award (RE: 202142-535001-20) to S.K.H. and NIH/NICHD 1 R01 HD046228 to A.A-H. The authors have no conflicts of interests. TRIAL REGISTRATION NUMBER: Not applicable.